2016
DOI: 10.1101/cshperspect.a026252
|View full text |Cite
|
Sign up to set email alerts
|

TP53Mutations in Breast and Ovarian Cancer

Abstract: Breast and ovarian cancers are the second and fifth leading causes of cancer deaths among women. Both breast and ovarian cancers are highly heterogeneous and are presented with diverse morphology, natural history, and response to therapy. In recent years, international efforts have led to extensive molecular characterization of both breast and ovarian tumors and identified biologically and clinically relevant subtypes of the diseases based on these molecular features. The role of TP53 in tumor initiation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 88 publications
3
119
0
Order By: Relevance
“…No statistically significant difference was observed between the survival outcomes of the other cancer types harboring TP53 mutations (Supplemental Figure 1). For example, there was no survival difference when comparing TP53 mutations based on residual transcriptional activity in breast cancer, although it is well established that breast cancer patients with TP53 mutations have poorer outcomes compared with WT carriers (23,24). These findings might indicate that a TP53 mutation represents only 1 key factor in projecting survival in certain cancer types, which may also be subtype specific (25).…”
Section: Resultsmentioning
confidence: 98%
“…No statistically significant difference was observed between the survival outcomes of the other cancer types harboring TP53 mutations (Supplemental Figure 1). For example, there was no survival difference when comparing TP53 mutations based on residual transcriptional activity in breast cancer, although it is well established that breast cancer patients with TP53 mutations have poorer outcomes compared with WT carriers (23,24). These findings might indicate that a TP53 mutation represents only 1 key factor in projecting survival in certain cancer types, which may also be subtype specific (25).…”
Section: Resultsmentioning
confidence: 98%
“…At last, we also constructed a lncRNA-mRNA ceRNA network (Figure 4D). TP53 was a ceRNA of FAM83H-AS1 and mutations in the TP53 gene are still by far the most frequent genomic event in cancer genomes [22]. All the results indicated that FAM83H-AS1 maybe play its role by interacting with some OC-related coding genes and 6 miRNAs.…”
Section: Fam83h-as1-centric Lncrna-mirna Lncrna-protein and Lncrna-mmentioning
confidence: 89%
“…At last, we also constructed a lncRNA-mRNA ceRNA network ( Figure 4D). TP53 was a ceRNA of FAM83H-AS1 and mutations in the TP53 gene are still by far the most frequent genomic event in cancer genomes [22]. All the results indicated that FAM83H-AS1 maybe play its role by interacting with some OC-related coding genes and miRNAs.…”
Section: Fam83h-as1 Was Associated With Prognosis In Pan-cancer and Ocmentioning
confidence: 90%